The war in Syria and its impact on tourism resources (Lattakia province prototype) - وهبي صالح; حليمة عبد الكريم; مخلوف هنادي (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The war which began in 2011, significantly affected the tourism sector throughout the republic s lands and the Lattakia governorate had its share of these repercussion as it is a governorate that has natural cultural resources and active in tourism and the research aims to identify consequences of the war on the tourism sector in terms of losses Economic natural and human tourism resources and tourism movement and the and the research relied on statistics and data from directorates and government departments that invalidated the research and the research concluded that the unstable situation in addition to the in fringements or natural and cultural tourism resources that led to the exit of this resources from tourism investment in whole or in part which has a negative and direct impaction the tourism movement in the governorate.